SIFAT KIMIA, KEKERASAN DAN ORGANOLEPTIK STIK TAHU DENGAN SUBSTITUSI TEPUNG SUKUN - Tri Wahyuningsih; Nurhidajah Nurhidajah; Agus Suyanto (Jurnal Pangan dan Gizi, 2018)
Tofu is processed food which comes from soy, already familiar with society at large. Besides tasty and nutritious, tofu also have a economic value which is cheap. Therefore need a diversification of processed food. One of them is processed being tofu stik. Stik need a padding for processing, that is breadfruit flour. The purpose of this research is to determine the effect of additional breadfruit flour to the chemical character, hardness and organoleptic of tofu stik. The method of this research is experiments methods using completely randomized design (RAL) monofaktorial by a factor variation of additional 0% 10% 20% 30% 40%. The data of water content and the protein content analyzed by statistical ANOVA and followed by a further test of DUNCAN whereas the organoleptic analyzed with Friedman test and Wilcoxon test. Statistical analysis shows an influence from the addition of breadfruit flour against hardness, the protein content and organoleptic but no effect on water content, this shown with p value <0,05, which means no effect.